PERBEDAAN PERSEPSI PENGANTAR KEARIFAN SOLUSI - Harjanto, Rudy (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2008)
Advertising activity in practice should be conducted in full manner of social responsibility due  to  differentiated  of perception.  The appearance of advertisements expected to be executed  in line with ethics, and consumerism regulatory. Negative perceptions on advertising should be taken as control tools how to make advertisements could contribute in better  way to society The difference perceptions bridge wisdom of solution.